2019
DOI: 10.1016/j.mayocp.2018.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Coaching: A New Strategy for Coaching Patients Living With Multimorbidity and Organizing Their Care

Abstract: The prevalence of chronic conditions is growing; to date, 1 in 4 Americans lives with at least one chronic condition. In the population aged 65 years and older, most live with multiple chronic conditions, or multimorbidity. Coaching interventions have been widely touted as a potential way to prevent chronic illness and as a way to help patients better self-manage their chronic illnesses. Health and Wellness Coaching (HWC) is now a respected discipline that offers certification, and HWC for patients with chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Their findings indicated that those programs improved care processes, compared to usual care. In the most recent review, Boehmer et al [ 16 ] provided a summary of health and wellness coaching activities in the field of multi-morbidity and called for a new type of intervention, capacity coaching in 2019. Currently, there is no comprehensive systematic review of HC impact on a chronic condition from the angle of patient improvement and detail coaching characteristics, therefore, a systematic review of randomized clinical trials from a comprehensive angle assessing the effect of HC in people with chronic conditions is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings indicated that those programs improved care processes, compared to usual care. In the most recent review, Boehmer et al [ 16 ] provided a summary of health and wellness coaching activities in the field of multi-morbidity and called for a new type of intervention, capacity coaching in 2019. Currently, there is no comprehensive systematic review of HC impact on a chronic condition from the angle of patient improvement and detail coaching characteristics, therefore, a systematic review of randomized clinical trials from a comprehensive angle assessing the effect of HC in people with chronic conditions is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Information systems must be attuned to signals that care may have become overwhelming, e.g., poor fidelity to treatment programs, missed appointments, poor disease control. And patients and their families should receive support that goes beyond disease education (using low-literacy material and peer support [ 28 ] to include self-management training, social support [ 29 ] and capacity coaching [ 30 ]. What may arise is care capable of advancing patient health goals with the smallest treatment burden possible [ 12 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Capacity Coaching This model of coaching has been proposed as "subspecialized or a modified" type of HWC when providing coaching to patients with chronic conditions or multimorbidity. 30 approach. A potential confusion and lack of clarity exists among healthcare professionals in differentiating health, and wellness or well-being, and any other type of related coaching; the natural evolution and the differentiation between the two has led to defining a health coach to be more closely focused on the state of physical health, while wellness, well-being, or life coach is more focused on the expanded state of happiness and content about one's being that encompasses various components, including physical, spiritual, emotional, financial, intellectual, environmental, and occupational wellness.…”
Section: Ahncc Icf Ccementioning
confidence: 99%
“…Capacity Coaching, a novel model of coaching, has been recently proposed as "subspecialized" type of HWC that provides coaching to patients with chronic conditions or multimorbidity. 30 Capacity Coaching builds its model on the work of MDM and aims to understand workload-capacity balance or imbalance that affects patients' abilities. It also explores resources to access and use healthcare and enact self-care, which in turn affects their outcomes.…”
Section: Patients Withmentioning
confidence: 99%